Does Early Postoperative T1 Slope Change Affect Clinical Results of Patients With Single-level ACDF?. Issue 9 (November 2021) - Guo, Yingjun; Liu, Hao; Meng, Yang; Wang, Xiaofei; Yang, Yi; Ding, Chen; Wang, Beiyu
Abstract : Study Design: This was a retrospective study. Objective: The main question of this study is whether the change of postoperative T1 slope will affect the clinical and imaging recovery of patients with single-level anterior cervical discectomy and fusion (ACDF). Summary of Background Data: The T1 slope after ACDF is different from that preoperatively, however, the clinical significance of this change has not been reported. Materials and Methods: A retrospective analysis was conducted on 87 patients with single-level ACDF. Visual Analogue Scale was used to compare neck and upper limb pain before and after surgery. Neurological improvement was assessed by the Japanese Orthopaedic Association Scores and Neck Disability Index. Preoperative and postoperative T1 slope, occipital-C2 angle, C2–C7 overall curvature and functional spinal unit curvature were measured and analyzed by lateral cervical spine x-ray. Results: All patients were followed up for 23.98±12.17 months. The Japanese Orthopaedic Association, Visual Analogue Scale, and Neck Disability Index scores as well as the overall curvature and change of C2–C7 and functional spinal unit were significantly improved in the last postoperative follow-up. At 12 months after surgery and the last follow-up, patients with increased T1 slope had more severe neck pain symptoms than those with decreased T1 slope ( P <0.05). The overall curvature and change of C2–C7 in patients with increased T1 slope were better than those with decreased T1 slope ( P <0.05). Conclusion: For patients with increased postoperative T1 slope after single-level ACDF, the degree of postoperative neck pain was more severe, suggesting that some clinical intervention is needed.